2014
DOI: 10.1002/ijc.29219
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of vegetables and fruits and risk of subtypes of head–neck cancer in the Netherlands Cohort Study

Abstract: There is limited prospective data on the relationship between consumption of vegetables and fruits and the risk of head-neck cancer (HNC) subtypes [i.e., oral cavity cancer (OCC), oro-/hypopharyngeal cancer (OHPC) and laryngeal cancer (LC)]. Therefore, we investigated these associations within the Netherlands Cohort Study, in which 120,852 participants completed a 150-item food frequency questionnaire at baseline in 1986. After 20.3 years of follow-up, 415 cases of HNC (131 OCC, 88 OHPC, three oral cavity/phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…These subtypes comprised mostly OSCCs and had an overrepresentation of female patients, matching the clinical description of elusive atypical HNSCC (Chaturvedi et al, 2013, Toner and O'Regan, 2009, MacKenzie et al, 2000, Patel et al, 2011, Koch et al, 1999, Koo et al, 2013, Brown et al, 2012, Montero et al, 2012, Perry et al, 2015). Epidemiological evidence indicates that smoking is less of a risk factor for OSCC than it is for LSCC (Maasland et al, 2014, Maasland et al, 2015). Consistent with this, we have found that LSCCs are primarily (though not exclusively) found in the smoking-related MethylMix subsets, while OSCCs are more heterogeneous and can be smoking-related, HPV-related, or atypical.…”
Section: Discussionmentioning
confidence: 99%
“…These subtypes comprised mostly OSCCs and had an overrepresentation of female patients, matching the clinical description of elusive atypical HNSCC (Chaturvedi et al, 2013, Toner and O'Regan, 2009, MacKenzie et al, 2000, Patel et al, 2011, Koch et al, 1999, Koo et al, 2013, Brown et al, 2012, Montero et al, 2012, Perry et al, 2015). Epidemiological evidence indicates that smoking is less of a risk factor for OSCC than it is for LSCC (Maasland et al, 2014, Maasland et al, 2015). Consistent with this, we have found that LSCCs are primarily (though not exclusively) found in the smoking-related MethylMix subsets, while OSCCs are more heterogeneous and can be smoking-related, HPV-related, or atypical.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been conducted to examine various other dietary components, patterns and indices in relation to oral and pharyngeal cancer 4551 . In the pooled analyses within the International Head and Neck Cancer Epidemiology Consortium folate 47 , vitamin C 45 , coffee and tea intake 48 were found to be protective against oral and pharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta-analyses based on 15 case-control and one cohort studies revealed a protective role of fruit and vegetables consumption 49 . In the Netherlands Cohort Study, an inverse association was observed between intake of nutrients like vitamin C and food items like fruits and vegetables; and the incidence of head and neck cancers including oral cancers 50, 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, allium vegetables contain several bioactive substances, such as organosulfur compounds and flavonoids, with anticarcinogenic properties against several types of cancers [3], including those of the colorectum [4], stomach [5], endometrium [6], and prostate [7].The association between allium vegetable intake and UADT cancers, mainly SCC, has been considered in several studies, with controversial results. The largest prospective study, the Netherlands Cohort Study considering 415 cases of head and neck cancers, found no relation with total allium and onion intake [8]. No consistent association was found also in other cohort studies from Europe [9,10].…”
mentioning
confidence: 82%